Children drawing violence: To what extent does it reflect actual experience. (November 2020) - Lev-Wiesel, Rachel; Hazan, Meital; Daniel, Milanya; German, Vera; Finger, Zeeva; Weinger, Susan; Binson, Bussakorn
Highlights: Children express their perceptions and actual experience of violence in drawings and narratives. Use of drawings encourage and enrich children's narratives. Innovative method to analyze drawings according to content and style, is presented. Relationship between level of symptomatology and severity of the drawn form of violence. The usefulness of using drawing to express perception of violence within a treatment framework is presented. Abstract: Violence against children is a prevalent worldwide phenomenon. Based on evidence that drawings may reveal unconscious conflicts and difficulties, the current study examined violence as reflected in children's drawings and narratives. Specifically, the study attempted to determine the extent to which the drawings and narratives express the child's personal experience of violence. A convenient sample consisted of 83 children (age range 8–12) drawn from community centers located in low-income communities. Participants were asked to draw what violence is for them then provide a narrative. Following the drawing, a self-report anonymous questionnaire consisted of three measures, demographics, traumatic events (6 events), and the Medical Somatic Dissociation Questionnaire (MSDQ), was administered. The drawings and the narratives were analyzed according to a phenomenological method. Latent class analysis (LCA) to identify the number of homogenous subgroups according to pictorial features within the overall sample yielded two clusters. Comparison between the clusters indicated that: Drawings of cluster 2 revealed more direct violence including the interaction between the perpetrator and victim and a specific form of violence, whereas drawings of cluster 1 revealed emotional symbols. No demographical, nor MSDQ differences were found between the clusters. Higher-level MSDQ scores were found in participants who reported physical abuse and hospitalization experiences and drew schematic figures. The drawings and narratives were not akin with one another.